Pengaruh Online Customer Review dan Social Media Marketing terhadap Keputusan Pembelian melalui Brand Image pada Kopi Toko Djawa Bandung - Avesina, Raditya Elfairuz; Madiawat, Putu Nina (eProceedings of Management, 2024)
The growth of the coffee shop industry has been accompanied by technological developments where this technologyhas been applied to people's daily lives so that technology has become an instrument for expanding businessopportunities in reaching a wider range of customers and promoting coffee shop products. This research aims todetermine the influence of Online Customer Reviews and Social Media Marketing on Purchase Decisions via BrandImage at Kopi Toko Djawa Bandung. The method used in this research is a quantitative method with descriptiveanalysis and using Structural Equation Modeling (SEM) which utilizes the SmartPLS 3.0 application. Then the resultof this research is the online customer review variable. The result of this study that are online customer review (X1)has a negative and significant influence on brand image (Y), social media marketing (X2) has a positive and significantinfluence on brand image (Y), brand image (Y) has a positive and significant influence on purchase decision (Z),online customer review (X1) has a negative and significant influence on purchase decision (Z) through brand image(Y), and social media marketing (X2) has a positive and significant influence on purchase decision (Z) through brandimage (Y).Keyword-online customer review, social media marketing, brand image, purchase decision